TorakochirurgiaDescending necrotizing mediastinitis – diagnosis and surgical treatment - Rokicki, Marek; Rokicki, Wojciech; Rokicki Jr, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Descending necrotizing mediastinitis (DNM) is believed to be a rare and serious complication of odontogenic and oropharyngeal infections. On the basis of literature and own experience we present criteria for diagnosis and classification of DNM, operative procedures including neck incision, radical surgical debridement of the mediastinum and thoracic cavity and drainage for mediastino-pleural irrigation. We suggest that the treatment strategy for severe DNM is early detection, immediate thoracotomy and irrigation of the mediastinum and thoracic cavity.